2018
DOI: 10.1088/1751-8121/aaf1e2
|View full text |Cite
|
Sign up to set email alerts
|

Critical O(N) model to orderϵ4from analytic bootstrap

Abstract: We compute, using the method of large spin perturbation theory, the anomalous dimensions and OPE coefficients of all leading twist operators in the critical O(N ) model, to fourth order in the -expansion. This is done fully within a bootstrap framework, and generalizes a recent result for the CFT-data of the Wilson-Fisher model. The anomalous dimensions we obtain for the O(N ) singlet operators agree with the literature values, obtained by diagrammatic techniques, while the anomalous dimensions for operators i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 63 publications
1
79
0
Order By: Relevance
“…The new results for OPE coefficients in this paper make it possible to perform similar consistency checks for the currents J ( ) R to order 4 /N 2 in all representations and for all spins. Using the 4− expansions computed in [38] we find perfect agreement. Unfortunately this does not give any constraint on the function ρ 1 (h, µ), since it does not appear until order 5 /N 2 , which can be seen from the explicit prefactor (γ (1) ϕ ) 2 /(µ − 2) 2 ∼ 2 in (F.1) and the additional factor (µ − 2) 3 ∼ 3 in the series (3.35).…”
Section: Irrep Spinmentioning
confidence: 58%
See 4 more Smart Citations
“…The new results for OPE coefficients in this paper make it possible to perform similar consistency checks for the currents J ( ) R to order 4 /N 2 in all representations and for all spins. Using the 4− expansions computed in [38] we find perfect agreement. Unfortunately this does not give any constraint on the function ρ 1 (h, µ), since it does not appear until order 5 /N 2 , which can be seen from the explicit prefactor (γ (1) ϕ ) 2 /(µ − 2) 2 ∼ 2 in (F.1) and the additional factor (µ − 2) 3 ∼ 3 in the series (3.35).…”
Section: Irrep Spinmentioning
confidence: 58%
“…A conformal block decomposition of this can be performed using the subleading corrections to the conformal blocks G τ, (z,z). The functional form of these block corrections is known [14], and by imposing the Casimir equation, they can be computed systematically order by order in z; for a short summary, see [38]. We have computed the OPE coefficients order by order, and found that they satisfy…”
Section: Contribution From [σ σ] Nmentioning
confidence: 99%
See 3 more Smart Citations